Museums, moralities and human rights - Sandell, Richard 1967- (Museum meanings, 2017)
"This book explores how museums, galleries and heritage sites of all kinds...through the narratives they construct and publicly present...contribute to shaping the moral and political climate within which human rights are experienced, continually sought and fought for, realised and refused. Through a series of richly-drawn cases and a focus on same-sex love and desire and gender diversity, Richard Sandell examines the ways in which museums are implicated in the ongoing struggle for lesbian, gay, bisexual, transgender and intersex human rights. Museums, Moralities and Human Rights offers new insights by bringing together, for the first time, the perspectives and experiences not only of those who work in, govern, fund and visit museums but also those of rights activists and campaigners who, at key moments in their struggle, have turned their attention to museums to advance their cause"...Provided by publisher